Three-Dimensional (3D) Animation and Calculation for the Assessment of Engaging Hill-Sachs Lesions With Computed Tomography 3D Reconstruction - Jimmy Tat, M.D., M.Sc; Jordan Crawford; Jaron Chong, M.D; Tom Powell, M.D; Thomas G. Fevens, Ph.D; Tiberiu Popa, Ph.D; Paul A. Martineau, M.D (Elsevier, 2021)
Purpose: To dynamically assess for Hill-Sachs engagement with animated 3-dimensional (3D) shoulder models. Methods: We created 3D shoulder models from reconstructed computed tomography (CT) images from a consecutive series of patients with recurrent anterior dislocation. They were divided into 2 groups based on the perceived Hill-Sachs severity. For our cohort of 14 patients with recurrent anterior dislocation, 4 patients had undergone osteoarticular allografting of Hill-Sachs lesions and 10 control patients had undergone CT scanning to quantify bone loss but no treatment for bony pathology. A biomechanical analysis was performed to rotate each 3D model using local coordinate systems to the classical vulnerable position of the shoulder (abduction = 90°, external rotation = 0-135°) and through a functional range. A Hill-Sachs lesion was considered "dynamically" engaging if the angle between the lesion's long axis and anterior glenoid was parallel. Results: In the vulnerable position of the shoulder, none of the Hill-Sachs lesions aligned with the anterior glenoid in any of our patients. However, in our simulated physiological shoulder range, all allograft patients and 70% of controls had positions producing alignment. Conclusions: The technique offers a visual representation of an engaging Hill-Sachs using 3D-animated reconstructions with open-source software and CT images. In our series of patients, we found multiple shoulder positions that align the Hill-Sachs and glenoid axes that do not necessarily meet the traditional definition of engagement. Identifying all shoulder positions at risk of "engaging," in a broader physiological range, may have critical implications toward selecting the appropriate surgical management of bony defects. Level of Evidence: level III, case-control study.